Comment on â€œStatus of Pathology Professionalsâ€ - Jha, R; Shrestha, A; Pant, A; Adhikari, R C; Karki, S (Journal of Nepal Health Research Council, 2012)
In 2012 Jan issue, Journal of Nepal Health Research Council published an article â€œStatus of Pathology Professionalsâ€ by Mishra SK affiliated to Concern for Public Health and Development (C-PHD), Kathmandu, Tiwari BR affiliated to Department of Clinical Microbiology, Peopleâ€™s Dental College, Tribhuwan University and Yadav BK from Department of Clinical Biochemistry, Institute of Medicine, Kathmandu, TribhuwanUniversity, Nepal.As a result, comments were sent to JNHRC, and are published below. Mishra SK, Tiwari BR, Yadav BK. Status of Pathology Professionals. J Nepal Health Res Counc 2012 Jan;10(20):37-40. PMID: 22929635.